Variability of convective activity over the Bay of Bengal and the Arabian sea - PATTANAIK, DR (MAUSAM, 2008)
The present study is an attempt to examine seasonal and interannual variability of convective activity over the north Indian Ocean. The monthly mean Outgoing Long-wave Radiation (OLR) data obtained from National Oceanic and Atmospheric Administration (NOAA) polar orbiting spacecraft are used in this study for a period of 26 year (1979 to 2004). The period has been divided into two groups of 13 years each with period (i) from 1979 to 1991 and period (ii) from 1992 to 2004. The monthly and seasonal variation of convective activity along with its linear trends analysis during four seasons [winter, Jan-Feb (JF); pre-monsoon, Mar-May (MAM); monsoon, Jun-Sep (JJAS); & post-monsoon, Oct-Dec (OND)] are performed. The difference of seasonal OLR anomalies in winter season between period (ii) & period (i) indicate increase in convective activity during recent period [period (ii)] compared to that of period (i) over the south Arabian Sea & south Bay of Bengal and just the opposite occurred over the rest regions associated with a significant decreasing trend of convective activity over the north and central Arabian Sea (at 99.9% level and 99% level respectively). During MAM the Bay of Bengal and the eastern part of Arabian Sea are relatively more convective during the recent period compared to the former period with significant increasing trend of convective activity over central Bay of Bengal (99% level) and northern (95% level) Bay of Bengal. The convective activity increases mainly over the southern parts of the Arabian Sea (dominated in the month of July) and some parts of southern and eastern Bay of Bengal in recent period compared to that of former period during the monsoon season and is associated with significant increasing trend (at 95 % level) of convective activity over the north Bay of Bengal. The post monsoon season also shows significant (at 95% level) increasing trend in convective activity over south Arabian Sea.